DAMPAK KENAIKAN HARGA PUPUK NON SUBSIDI TERHADAP USAHATANI PADI DI DESA SALEH MAKMUR KECAMATAN AIR SALEK KABUPATEN BANYUASIN - Usman, Ali; Iswarini, Harniatun (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2024)
ABSTRACTThis study aimed to determine the fluctuations in non-subsidized fertilizer prices from 2019 to 2023, identify the impact of these price increases on the availability of non-subsidized fertilizers for rice farmers, and understand the effect on the dosage of non-subsidized fertilizers used on rice crops. The research was conducted in Desa Saleh Makmur, Kecamatan Air Salek, Kabupaten Banyuasin, from January to May 2024. A descriptive qualitative research method with a survey approach was used. The sampling method employed was simple random sampling, with a total sample size of 25 farmers using non-subsidized fertilizers and 5 fertilizer traders. Data were collected through observation, interviews, and documentation. Data processing involved data condensation, presentation, description, and drawing conclusions, utilizing qualitative descriptive analysis. The study results showed that the prices of Urea and Phonska fertilizers experienced significant fluctuations during the 2019-2023 period, especially in 2020-2021, before stabilizing in 2023. Factors contributing to the price increases included rising transportation costs, high demand during planting seasons, government policies, and global market conditions. Further findings indicated that these price increases significantly impacted the availability of non-subsidized fertilizers by increasing production costs, reducing farmers' profit margins, and causing traders to reduce fertilizer stock and adopt more cautious inventory management to avoid losses. The study also found that the rise in non-subsidized fertilizer prices significantly affected fertilizer usage by rice farmers, with many reducing their usage from 1 sack of urea and 2 sacks of Phonska per hectare to 1 sack of urea and 1 sack of Phonska per hectare, though some farmers continued using the same dosage. ABSTRAKPenelitian ini bertujuan untuk mengetahui fluktuasi harga pupuk non-subsidi pada tahun 2019-2023, dampak kenaikan harga pupuk non-subsidi terhadap ketersediaan pupuk non-subsidi bagi petani padi, serta dampak kenaikan harga terhadap dosis penggunaan pupuk pada tanaman padi di Desa Saleh Makmur, Kecamatan Air Salek, Kabupaten Banyuasin. Penelitian ini dilaksanakan dari Januari hingga Mei 2024 dengan menggunakan metode deskriptif kualitatif dan jenis penelitian survei. Metode penarikan contoh menggunakan simple random sampling dengan 25 petani dan 5 pedagang pupuk sebagai sampel. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Data diolah melalui kondensasi data, penyajian data, dan penarikan kesimpulan menggunakan analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa harga pupuk jenis Urea dan Phonska mengalami fluktuasi signifikan pada periode 2019-2023, terutama pada tahun 2020-2021, sebelum akhirnya stabil pada 2023. Faktor yang menyebabkan kenaikan harga antara lain kenaikan biaya transportasi, permintaan tinggi selama musim tanam, kebijakan pemerintah, dan kondisi pasar global. Kenaikan harga ini berdampak pada ketersediaan pupuk non-subsidi, dengan meningkatkan biaya produksi, mengurangi margin keuntungan petani, dan membuat pedagang lebih berhati-hati dalam pengelolaan stok. Selain itu, kenaikan harga pupuk non-subsidi juga mempengaruhi dosis penggunaan pupuk oleh petani padi, yang sebelumnya menggunakan 1 karung urea dan 2 karung Phonska per hektar, menjadi 1 karung urea dan 1 karung Phonska per hektar, meskipun masih ada petani yang tetap menggunakan dosis yang sama.